2001
DOI: 10.1002/gene.1051
|View full text |Cite
|
Sign up to set email alerts
|

Pitx1 and Pitx2c are required for ectopic cement gland formation in xenopus laevis

Abstract: Summary: The mucus secreting cement gland is the anterior-most ectodermal organ of the Xenopus embryo. The homeobox genes Pltx1 and Pitx2c are expressed in the cement gland primordium. Misexpression of both genes induced ectopic cement gland tissue in whole embryos and transcription of the marker genes Xag1 and Xag2 in animal cap explant cultures. Antisense morpholino oligonucleotides against Pitx1 and Pitx2c inhibited ectopic cement gland formation induced by otx2. Gene knock downs generated by morpholino oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…By that time, the CG starts to express proteins such as anterior gradient (xAgr) that are used as CG markers and are important for the gland's secreting function (7,8). The positioning and inducing of the CG relies on the expression of orthodenticle homeobox 2 (Otx2) and pituitary homeobox (Pitx) genes (2,(8)(9)(10)(11)(12), whereas adequate levels of bone morphogenic protein 4 (Bmp4) signals are permissive for its development (13).…”
mentioning
confidence: 99%
“…By that time, the CG starts to express proteins such as anterior gradient (xAgr) that are used as CG markers and are important for the gland's secreting function (7,8). The positioning and inducing of the CG relies on the expression of orthodenticle homeobox 2 (Otx2) and pituitary homeobox (Pitx) genes (2,(8)(9)(10)(11)(12), whereas adequate levels of bone morphogenic protein 4 (Bmp4) signals are permissive for its development (13).…”
mentioning
confidence: 99%
“…Furthermore, knocking down of Pitx1 and Pitx2c inhibits ectopic cement gland formation induced by Otx2 (Schweickert et al . ). Additionally, it has been suggested that Pitx genes act downstream of Otx2 during the development of the cement gland (Dickinson & Sive ).…”
Section: Discussionmentioning
confidence: 97%
“…) and that Pitx genes act downstream of Otx2 in the cement gland formation (Schweickert et al . ; Dickinson & Sive ). In the teleost fish, Astyanax mexicanus , the casquette, which is formed on the head of its larvae, is regarded to be homologous to the cement gland in Xenopus (Pottin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Molecules that function as antagonists of BMP4, including noggin and chordin, can cause ectoderm to form either anterior neural tissue or cement gland, depending on the dose each cell receives (Knecht et al, 1995;Wilson et al, 1997). Cement gland can also be formed from ectoderm in response to molecules that are not potent neural inducers, including Pitx1, Pitx2c, Xotx5b (Chang et al, 2001;Schweickert et al, 2001;Vignali et al, 2000), and now, GREUL1. In ectodermal explants, these molecules are able to activate the expression of Xotx2 and XAG-1 without significant neural marker induction (Chang et al, 2001;Vignali et al, 2000).…”
Section: Discussionmentioning
confidence: 99%